Towards Precision Diagnosis: Thoughts and Suggestions on Enhancing the Nomogram for Ventilator-Associated Pneumonia [Response to Letter] - Yang J; Li Y; Wang Y (Journal of Inflammation Research)
Jiajia Yang,1 Yuancheng Li,2 Ying Wang1 1Department of Infection Management, The Affiliated Suzhou Hospital of Nanjing Medical University, Suzhou Municipal Hospital, Gusu School, Nanjing Medical University, Suzhou, 215008, People’s Republic of China; 2Institute of Dermatology, Chinese Academy of Medical Sciences and Peking Union Medical College, Jiangsu Key Laboratory of Molecular Biology for Skin Diseases and STIs, Nanjing, 210042, People’s Republic of ChinaCorrespondence: Ying Wang, Department of Infection Management, The Affiliated Suzhou Hospital of Nanjing Medical University, Suzhou Municipal Hospital, Gusu School, Nanjing Medical University, No. 242, Guangji Road, Suzhou, 215008, People’s Republic of China, Email wangy830224@sina.com